Research on the Pump Shaft Stability Analysis of Multistage Centrifugal Pump During Closed-Valve Start-Up Process - Long, Yun; Lin, Bin; Fang, Jie; Ge, Jie; Xu, Longbo; Fu, Qiang; Zhu, Rongsheng (Frontiers in Energy Research, 2020)
In order to analyze the pump shaft stability of multistage centrifugal pump during the closed-valve start-up process, the transient internal fluid field and structural field during the closed-valve start-up process of the TDM 35-140 × 13 segmental multistage centrifugal pump are solved by transient fluid-solid coupling. The transient deformation and vibration velocity of the pump shaft are analyzed. It is found that the maximum deformation amount of the third stage impeller and the pump shaft cylindrical contact surface (N = 7 node area) during the whole closed-valve transition start-up process is the largest. The maximum deformation in the region where the nodes 1 ≤ N ≤ 10 are significantly greater than that in other regions. In the 11 ≤ N ≤ 19 node, with the node position coordinate value N increasing, the maximum deformation amount is continuously decreasing. During the entire closed-valve transition start-up process, the vibration speed of the pump shaft fluctuates drastically. In the node of 1 ≤ N ≤ 19, with the node position coordinate value N increasing, the maximum vibration velocity first increases and then decreases. The maximum vibration speed at N = 11 nodes is higher than that of all other nodes.